2006
DOI: 10.1074/jbc.m507378200
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated Protein MAP1A, MAP1B, and MAP2 Proteolysis during Soluble Amyloid β-Peptide-induced Neuronal Apoptosis

Abstract: A growing body of evidence supports the notion that soluble oligomeric forms of the amyloid ␤-peptide (A␤) may be the proximate effectors of neuronal injuries and death in the early stages of Alzheimer disease. However, the molecular mechanisms associated with neuronal apoptosis induced by soluble A␤ remain to be elucidated. We recently demonstrated the involvement of an early reactive oxygen species-dependent perturbation of the microtubule network (Sponne, I., Fifre, A., Drouet, B., Klein, C., Koziel, V., Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 97 publications
5
90
0
2
Order By: Relevance
“…In this case, about 70% of retinal neurons that had very low levels of MAP-2 following siRNA transfection were detected as TUNEL-positive due to a sublethal exposure to ROS. This observation is in agreement with previous studies that demonstrated reduction of MAP-2 in degenerating neurons induced by ROS-generating agents in vitro or ischemia in vivo (Wang et al, 2001;Fifre et al, 2006). Although the discrepancy of glial support might indirectly intervene neuronal surviving in the presence of TMP, retaining of the neuronal specific MAP-2 protein in neuronal soma by TMP appeared to increase specifically the resistance of neurons to attacks.…”
Section: Discussionsupporting
confidence: 93%
“…In this case, about 70% of retinal neurons that had very low levels of MAP-2 following siRNA transfection were detected as TUNEL-positive due to a sublethal exposure to ROS. This observation is in agreement with previous studies that demonstrated reduction of MAP-2 in degenerating neurons induced by ROS-generating agents in vitro or ischemia in vivo (Wang et al, 2001;Fifre et al, 2006). Although the discrepancy of glial support might indirectly intervene neuronal surviving in the presence of TMP, retaining of the neuronal specific MAP-2 protein in neuronal soma by TMP appeared to increase specifically the resistance of neurons to attacks.…”
Section: Discussionsupporting
confidence: 93%
“…As a result of this work, it has been shown that dynamin 1 was significantly reduced not only in the hippocampus of an AD mouse model and in cultured hippocampal neurons treated with Aβ but also in the brain of AD patients (Yao et al 2003;Kelly et al 2005;Kelly and Ferreira 2006). The mechanisms leading to this dynamin 1 depletion seem to involve calpain, a protease system that is active in AD (Tsuji et al 1998;Lee et al 2000;Battaglia et al 2003;Tomizawa et al 2003;Chen and Fernandez 2005;Demuro et al 2005;Gong et al 2005;Kelly et al 2005;Fifre et al 2006;Kelly and Ferreira 2006). Furthermore, we have reported that this Aβ-mediated dynamin 1 degradation was the result of calpain activation induced by the sustained calcium influx mediated by N-methyl-D-aspartate (NMDA) receptors in hippocampal neurons (Kelly and Ferreira 2006).…”
Section: Discussionmentioning
confidence: 78%
“…MAP-2 is a microtubule-associated protein that has been shown to be decreased in some models of neurodegeneration and AD. 33,34 In particular, it was reported that rats fed with a high-fat diet (soybean oil and cholesterol supplemented, no fructose) for 8 weeks present a diminished staining of MAP-2 in the hippocampus, and that this reduction is correlated with memory errors. 16 Microtubule-associated protein 2 modifies and controls microtubule assembly and spacing within dendrites.…”
Section: Discussionmentioning
confidence: 99%